PELATIHAN PUBLIC SPEAKING UNTUK MENINGKATKAN RASA PERCAYA DIRI PADA ANAK REMAJA DI DESA KEDUNGTURI TAMAN SIDOARJO - Nailul Ulah Al Chumairoh Machfud; Erni Wijayanti; Ananda Ainia Anjani (AlMurtado Journal of Social Innovation and Community Service, 2025)
Language is used to communicate with two or more people with various ideas, experiences, and feelings through writing, oral, and so on. A person who cannot communicate well can become less confident when speaking in public. Panic arises and is very disturbing for those who are afraid. An unprepared body will show panic symptoms due to the pressure that has just arisen before starting to speak in public. Lack of practice and getting used to public speaking is one of the reasons why there is a sense of nervousness when performing. The purpose of this service is to increase the confidence of teenagers in Kedutungturi Village, Taman Sidoarjo through public speaking training. It is hoped that with this activity, teenagers in Kedungturi Village, Taman Sidoarjo can have knowledge, understanding and skills about the science of Public Speaking to gain a better understanding of the public speaking method and to apply it.